2020
DOI: 10.1136/bmjebm-2020-111521
|View full text |Cite
|
Sign up to set email alerts
|

Teaching clinicians shared decision making and risk communication online: an evaluation study

Abstract: ObjectivesTo describe the development and initial evaluation of a brief e-learning course as a means of teaching shared decision making and risk communication skills to clinicians of all specialties.DesignComparison pre-course and post-course of scores in subjective confidence and objective knowledge about shared decision making and risk communication.SettingOnline and open to all specialties and levels of clinical experience, including students.ParticipantsThe course is freely available online and all who sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 42 publications
0
15
1
Order By: Relevance
“…Another German study noted that the regular use of eHealth services facilitated the decision-making process for patients with cancer and their families [ 40 ]. Other studies have reported that the internet and web-based courses are fundamental in improving patients’ communication skills with medical personnel [ 3 , 41 ], reducing their overall medical expenses [ 42 ], and increasing their confidence and knowledge to be involved in decision-making [ 43 ]. In addition, we found that patients who reported being very satisfied with SDM (satisfied with all five dimensions of the SSDM) obtained a similar mean score on the eHEALS ( Multimedia Appendix 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another German study noted that the regular use of eHealth services facilitated the decision-making process for patients with cancer and their families [ 40 ]. Other studies have reported that the internet and web-based courses are fundamental in improving patients’ communication skills with medical personnel [ 3 , 41 ], reducing their overall medical expenses [ 42 ], and increasing their confidence and knowledge to be involved in decision-making [ 43 ]. In addition, we found that patients who reported being very satisfied with SDM (satisfied with all five dimensions of the SSDM) obtained a similar mean score on the eHEALS ( Multimedia Appendix 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…This could be a key message in training programmes. An up-to-date systematic review of studies evaluating the effectiveness of recently developed shared decision-making training is warranted (91)(92)(93).…”
Section: Implications For Research and Practicementioning
confidence: 99%
“…For example, a 2-hour interactive e-learning course on shared decision making (which has a version for GPs) appears to improve clinicians' shared decisionmaking confidence and knowledge, but behavioral effects are not yet tested. 23…”
Section: Implications For Practice and Researchmentioning
confidence: 99%